A checklist of the Cleridae of Iran with new data (Coleoptera: Cleroidea) - Zappi, Iuri; Ghahari, Hassan (Zootaxa, 2016)
Species diversity of Iranian Cleridae (Coleoptera: Cleroidea) is summarized in this paper. A total of 48 species and 1 subspecies in 14 genera belonging to 4 subfamilies of Cleridae are recorded. Eight species, Thaneroclerus buqueti (Lefebvre, 1835), Denops albofasciatus (Charpentier, 1825), Flabellotilloidea palaestina (Pic, 1900), Clerus mutillaroides Reitter, 1894, Opilo cilicicus Hintz, 1902, Opilo longipilis Fairmaire, 1892, Trichodes alberi Escherich, 1894 and Trichodes inermis Reitter, 1894 are recorded from Iran for the first time. Synonymies and distribution data are given. The checklist is based on examination of the literature and also includes records from specimens examined in many collections. Taxa are arranged hierarchically under the categories of subfamily, genus, species and subspecies.